Vegetation responses to 2012-2016 drought in Northern and Southern California - Dong, Chunyu; MacDonald, Glen M.; Willis, Kathy J.; Gillespie, Thomas; Okin, Gregory S.; Williams, A. Park (Geophysical research letters, 2019)
The prolonged 2012-2016 California drought has raised many issues including concerns over reduced vegetation health. Drought impacts are complicated by geographical differences in hydroclimatic variability due to a climatic dipole influenced by the Pacific. Analysis of MODIS-derived Normalized Difference Vegetation Index and self-calibrated Palmer Drought Severity Index from 2000 to 2018 reveals differences in drought and vegetation responses in Northern versus Southern California (NorCal vs SoCal, see definition in section ). The greatest declines in Normalized Difference Vegetation Index were focused in the SoCal, while NorCal appears not severely affected thus far. It appears that both the strength of drought and the sensitivity of the vegetation to drought are larger in SoCal. The exacerbated aridity in SoCal is a trend extending throughout the past and present century. The spatial differences in hydroclimatology and vegetation responses are important considerations for statewide climate change adaptation—with SoCal potentially facing greater challenges.
Gesehen am 06.05.2022